2013
DOI: 10.1111/jeb.12277
|View full text |Cite
|
Sign up to set email alerts
|

Individual vocal signatures in barn owl nestlings: does individual recognition have an adaptive role in sibling vocal competition?

Abstract: To compete over limited parental resources, young animals communicate with their parents and siblings by producing honest vocal signals of need. Components of begging calls that are sensitive to food deprivation may honestly signal need, whereas other components may be associated with individualspecific attributes that do not change with time such as identity, sex, absolute age and hierarchy. In a sib-sib communication system where barn owl (Tyto alba) nestlings vocally negotiate priority access to food resour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 61 publications
3
29
2
Order By: Relevance
“…As in human conversation (Stivers et al, 2009), the basic turn-taking rules demonstrated here do not depend on family, context of the social interaction, age hierarchy or hunger level. Although seniority influences vocal production with juniors producing more, longer and louder calls than seniors (Dreiss, Lahlah, et al, 2010;Dreiss et al, 2014; present study), turn-taking rules are similar in junior and senior siblings. Turn-taking rules, which allow each individual to determine when and how to start signalling, have only been described in a cooperative vocal exchange, such as duetting birds (Logue, Chalmers, & Gowland, 2008) and contact calls in some monkeys (Biben, Symmes, & Masataka, 1986;Hauser & Fowler, 1992;Takahashi et al, 2013), during antiphonal exchange of rapid phrases.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…As in human conversation (Stivers et al, 2009), the basic turn-taking rules demonstrated here do not depend on family, context of the social interaction, age hierarchy or hunger level. Although seniority influences vocal production with juniors producing more, longer and louder calls than seniors (Dreiss, Lahlah, et al, 2010;Dreiss et al, 2014; present study), turn-taking rules are similar in junior and senior siblings. Turn-taking rules, which allow each individual to determine when and how to start signalling, have only been described in a cooperative vocal exchange, such as duetting birds (Logue, Chalmers, & Gowland, 2008) and contact calls in some monkeys (Biben, Symmes, & Masataka, 1986;Hauser & Fowler, 1992;Takahashi et al, 2013), during antiphonal exchange of rapid phrases.…”
Section: Resultsmentioning
confidence: 73%
“…The senior individual was 5 days older than its junior sibling on average (range in age difference 1e15 days). We examined the effect of seniority rather than absolute age, because previous studies showed that seniority has a stronger effect on vocalization than absolute age (Dreiss, Ruppli, Faller, & Roulin, 2013;Dreiss, Ruppli, & Roulin, 2014). Nestlings were kept in these boxes for 2 days and 3 nights and then returned to their original nest in the field.…”
Section: Recording Vocal Interactions Between Pairs Of Siblingsmentioning
confidence: 99%
See 1 more Smart Citation
“…PIC values represent the ratio of the coefficient of variance for the entire dataset to the within-individual coefficient of variance. Thus, a PIC value >1 indicates that a particular variable exhibits greater inter-individual than intra-individual variation, making it a likely candidate for containing individually distinc tive information (Charrier et al 2002, Dreiss et al 2014). …”
Section: Potential For Individuality Codingmentioning
confidence: 99%
“…Visual scanning of recordings were done to verify the accuracy of the method ; for an acoustic description of calls, see Dreiss et al 2014).…”
Section: Playback Experimentsmentioning
confidence: 99%